OP0198-HPR No prospective association found between obesity and chronic, widespread musculoskeletal pain in a population based 20-year prospective follow-up study. (23rd January 2014) - Magnusson, K.; Østerås, N.; Mowinckel, P.; Bård, N.; Hagen, K.B.
Abstract : Background: Chronic, widespread musculoskeletal pain (CWP) and obesity are common problems in today's society, and both are associated with impaired function and reduced quality of life. The cross-sectional association between CWP and obesity is well established, but the temporal relationship is poorly understood. Objectives: To investigate the prospective association between obesity and CWP. Methods: In a twenty year population based prospective cohort study (the "Musculoskeletal pain in Ullensaker Study"), a random sample (n=855) of persons between 20 and 62 years in 1990 living in the municipality Ullensaker in Norway, participated in postal surveys in 1990, 1994, 2004 and 2010. CWP was reported on the Standard Nordic Questionnaire, and defined as the number of pain sites during the past seven days in: head, neck, shoulder, elbow, hand/wrist, upper back, lower back, hip, knee and/or ankle/foot. The number of pain sites were summed up and used as a continuous variable in the analyses. Body Mass Index (BMI) was calculated by self-reported height and weight. BMI and CWP in 2010 were employed as dependent variables. Preselected covariates were sex, age, physical activity, smoking, mental distress, perceived health and sleep quality. To exploit all measurement times, a mixed models approach was used. Results: The mean age was 60 years in 2010 and 57.2% were females. Mean (sd) number of pain sites was 2.4 (2.3) and mean BMI was 25.9 (3.4) in 2010. BMI in 1990, 1994 and 2004 was not related to CWP in 2010, but female sex, poor perceived health, poor sleep quality and smoking were associated with a significantly higher number of pain sites (table 1 ). CWP in 1990, 1994 and 2004 was not related to obesity in 2010, but being male and poor perceived health were associated with higher BMI in 2010 (table 2). Conclusions: CWP and obesity did not mutually influence each other in this study, but perceived health predicted both conditions, and poor sleep was a predictor of more CWP. Although poor sleep has been found to predict obesity in previous studies, this was not found in this study. Future research should focus on the role health perception and sleep quality can have on the development of both CWP and obesity. Disclosure of Interest: None Declared